Ambient fine particulate matter induces cardiac fibrosis through triggering ferroptosis by heme degradation induced-iron overload - Jinjin Jiang; Yang Li; Yuping Chen; Qin Wu; Shibin Ding (Ecotoxicology and Environmental Safety)
Background: Previous studies have shown a significant correlation between exposure to ambient fine particulate matter (PM2.5) and cardiac fibrosis, yet the precise detrimental effects and underlying mechanisms of PM2.5 exposure on cardiac fibrosis remain incompletely understood. Cardiac remodeling, a process involving ferroptosis that can be initiated by iron overload, has been implicated in this phenomenon. In this study, we sought to explore the potential mechanism by which ferroptosis contributes to PM2.5-induced cardiac fibrosis. Methods and results: Male C57BL/6 J mice were exposed to ambient PM2.5 by intratracheal instillation twice a week for 12 weeks to establish PM2.5-exposed murine models and cardiomyocytes were used to verify the role of ferroptosis in PM2.5-induced cardiac fibrosis. In this study, it was observed that exposure to PM2.5 resulted in cardiac fibrosis and a significant upregulation of cardiac fibrosis-related markers (TGF-β1, collagen-I and p-Smad3), heme oxygenase 1 (HO-1), and ACSL4 (a biomarker for ferroptosis). Additionally, PM2.5 exposure led to a decrease in heme content, iron overload, increased levels of the lipid peroxidation marker 4-HNE, and a reduction in the ratio of GSH/GSSG and GPX4 (a biomarker for ferroptosis) in murine hearts. Significantly, the use of ferrostatin-1 (an inhibitor of ferroptosis) mitigated PM2.5-induced cardiac fibrosis and decreased the levels of cardiac fibrosis-related markers (TGF-β1, collagen-I and p-Smad3) in murine hearts, indicating the essential role of ferroptosis in the development of cardiac fibrosis. In vitro experiments showed that PM2.5 upregulated the expression of HO-1 protein, promoted iron accumulation, increased 4-HNE levels, and triggered ferroptosis in cardiomyocytes. The inhibition of HO-1 (zinc protoporphyrin 9) and siRNA HO-1 effectively mitigated PM2.5-induced iron overload, ferroptosis, and heme accumulation in cardiomyocytes. Additionally, treatment with ferrostatin-1 markedly decreased the expression levels of cardiac fibrosis-related markers, such as TGF-β1 and p-Smad3. Conclusion: Collectively, our study showed that the activation of ferroptosis/TGF-β1/Smad3 signaling pathway, initiated by heme degradation-induced iron overload in cardiomyocytes, serves as a mechanism in murine models of PM2.5-induced cardiac fibrosis.